Evaluación técnico financiera de diseño conceptual de un gasoducto entre Aguazul y Yopal que respalde el transporte de gas a Yopal (2018)
This degree work was developed with Delvasto & Echeverría company, the purpose was conceiving the conceptual design of a gas pipeline between the municipalities of Aguazul and the municipality of Yopal in the department of Casanare that is able to support and ensure the constant service of natural gas supply to the municipality of Yopal, due to the fact that the current pipeline (Floreña- Yopal) has constant damage to its infrastructure which generates suspension of natural gas service in the municipality. For the election of the final route of the gas pipeline, the previous proposal was made of three alternative routes based on a study of Bases Environmental Lines, a study of topography (planimetry and altimetry) and a field trip, this in order to know, observe and to specify criteria of high importance when proposing any of the alternatives of route such as: roads, bodies of water, populated areas, geological generalities, fauna and flora, to finally make a comparative evaluation and choose the most optimal route for the gas pipeline.